Highly Regioselective Phosphine-Promoted [2+2+2] Annulations of Cyanoacetylenes and N-Tosylimines to 1,2-Dihydropyridine-3,5-dicarbonitrile Derivatives - Zhang, Jinfeng; Zhang, Qi; Ji, Xin; Meng, Ling-Guo (Synlett, 2019)
A series of fully functionalized dihydropyridine-3,5-dicarbonitrile derivatives were easily prepared through [2+2+2] annulations of cyanoacetylenes and N-tosylimines in the presence of tertiary phosphine. The scope of the cyclization reaction was investigated, and the high regioselectivity was explained by a rational reaction mechanism.
Keywords: phosphine; annulations; cyanoacetylenes; N-tosylimines; regioselectivity